2020
DOI: 10.1111/1758-2229.12878
|View full text |Cite
|
Sign up to set email alerts
|

The highly crystalline PET found in plastic water bottles does not support the growth of the PETase‐producing bacterium Ideonella sakaiensis

Abstract: Summary Ideonella sakaiensis produces an enzyme, PETase, that is capable of hydrolyzing polyethylene terephthalate (PET) plastic. We demonstrate that although I. sakaiensis can grow on amorphous plastic, it does not grow on highly crystalline plastic under otherwise identical conditions. Both amorphous film and amorphous plastic obtained from commercial food containers support the growth of the bacteria, whereas highly crystalline film and the highly crystalline body of a plastic water bottle do not support gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…films (e.g. crystallinity 1.9% (Taniguchi et Wallace et al (2020) suggest that 52% to 82% of the plastic in PET water bottles is not amenable to microbial degradation without further treatment, due to the crystalline content of the polymer. PETase enzymes are one of the beststudied enzyme groups in reference to plastic polymer hydrolysis and biotechnological advances provide additional scope for enhanced polymer degradation or the production of high-value compounds from waste PET (Danso et al 2019).…”
Section: Synthesismentioning
confidence: 99%
“…films (e.g. crystallinity 1.9% (Taniguchi et Wallace et al (2020) suggest that 52% to 82% of the plastic in PET water bottles is not amenable to microbial degradation without further treatment, due to the crystalline content of the polymer. PETase enzymes are one of the beststudied enzyme groups in reference to plastic polymer hydrolysis and biotechnological advances provide additional scope for enhanced polymer degradation or the production of high-value compounds from waste PET (Danso et al 2019).…”
Section: Synthesismentioning
confidence: 99%
“…It follows that mesophilic Is PETase, despite its structural similarities to these cutinases and observed hydrolyzing activities at 30°C, should not be regarded as a PET hydrolase, particularly with respect to application ( Kawai et al, 2020 ). It was also recently demonstrated that while amorphous PET supports growth of I. sakaiensis , high crystallinity PET films and bottles do not (unless hcPET is melted and cooled rapidly to give amorphous plastic) ( Wallace et al, 2020 ). TfH may still be grouped with PET hydrolases as it was the first enzyme reported for efficient PET hydrolysis and it is thermophilic.…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…Low crystallinity results in better degradation. PET degrading I. sakaiensis can degrade amorphous PET but is unable to degrade high crystallinity PET ( Wallace et al, 2020 ). When the crystalline PET was converted to amorphous PET the bacterium again was able to degrade the compound ( Wallace et al, 2020 ).…”
Section: Diversity Of Synthetic Polymersmentioning
confidence: 99%